Non-Competitive Wage-Setting as a Cause of Unfriendly and Inefficient Leadership - Robert A. J. Dur; Ola Kvaløy; Anja Schöttner (Tinbergen Institute, 2018)
This paper develops a simple economic model to examine how leadership styles in organizations depend on the prevailing wage-setting conditions for workers. In particular, we examine a leader who can – in addition to the use of monetary incentives – motivate a worker by adopting leadership styles that differ in their non-monetary consequences for the worker's well-being. Some leadership styles produce non-monetary benefits for workers (such as those involving the provision of praise to high-performing workers), other styles impose non-monetary costs (such as those involving social punishment for low performers). We show that leaders never use the latter type of leadership when the worker is hired in a competitive labor market. In contrast, in labor markets with non-competitive wage-setting (e.g., in the presence of trade union bargaining or minimum wage legislation) leaders sometimes do use the 'unfriendly' style, and the more so the worse the worker's labor market prospects are. We show that this is socially inefficient. 'Friendly' leadership styles are always adopted when they are socially efficient.
Keywords: M5; 330; leadership styles; incentives; motivation; wage-setting